2007
DOI: 10.1159/000098720
|View full text |Cite
|
Sign up to set email alerts
|

Experiences in the Perinatal Management of Congenital Diaphragmatic Hernia during the Last 15 Years in a Tertiary Referral Institute

Abstract: Objective: Review of cases of perinatally diagnosed congenital diaphragmatic hernias with special regard to time of diagnosis, organs herniated into the thorax, associated malformations, and outcomes. Methods: We analyzed the data of 106 cases between July 1, 1990, and June 30, 2005. The observation period was analyzed in two parts. Results: Prenatal ultrasound was performed in 89.6% (95/106) of the cases. 51.7% (46/89) of the pre- and postnatally verified congenital diaphragmatic hernia cases were diagnosed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
0
7
0
1
Order By: Relevance
“…This allowed the calculation of the LPA to MPA (LPA/ MPA) ratio and RPA to MPA (RPA/MPA) ratio, which were independent of gestation. As a preliminary study, these branch PA diameters in the normal fetuses were compared with those in cases of congenital diaphragmatic hernia (CDH), which has a poor prognosis caused by pulmonary hypoplasia, even if found prenatally [10] .…”
mentioning
confidence: 99%
“…This allowed the calculation of the LPA to MPA (LPA/ MPA) ratio and RPA to MPA (RPA/MPA) ratio, which were independent of gestation. As a preliminary study, these branch PA diameters in the normal fetuses were compared with those in cases of congenital diaphragmatic hernia (CDH), which has a poor prognosis caused by pulmonary hypoplasia, even if found prenatally [10] .…”
mentioning
confidence: 99%
“…The survive rate of CDH in NICU appears, therefore, to be similar in comparison to recent studies in high-risk CDH patients, (6,13) but to be lower in comparison to some other studies in isolated CDH patients. (14,15) In our study, we compared CDH patients who survived with non-survivors, and found that survivors were associated with an excess NICU length of stay.…”
Section: Discussionmentioning
confidence: 98%
“…Çalışmamızda, cinsiyetle yaşam oranı arasında anlamlı ilişki saptanmamıştır. 106 olguluk bir çalışmada, C/S ile doğan olgularda sağkalım oranının vajinal yolla doğanlara göre 3 kat daha fazla olduğu saptanmıştır (22) . Bir çalışmada ise, doğum şeklinin sağkalımı etkilemediği saptanmamış-tır (23) .…”
Section: Discussionunclassified